Komunikasi Kebijakan Publik yang Efektif : Peran Public Affairs dalam Meningkatkan Pemahaman dan Partisipasi Masyarakat - Nur Azel Rizki Syahbani; Rachmandita Oktavian; Faris Aulia Riski; Tria Patrianti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Effective public policy communication is a crucial factor in ensuring public understanding, acceptance, and participation in the process from policy formulation to implementation. In this context, public affairs plays a strategic role as a liaison between policymakers and the public through information management, stakeholder relationship building, and facilitation of ongoing public dialogue. This study aims to analyze the role of public affairs in realizing effective public policy communication and its contribution to increasing public understanding and participation. The research method used is a descriptive qualitative approach with data collection techniques such as in-depth interviews, observation, and documentation of policy communication activities. The results show that public affairs strategies include policy publication, stakeholder engagement, media relations management, and the use of digital communication. However, obstacles remain, such as limited two-way communication and unequal levels of public understanding of policies. This study emphasizes the importance of strengthening participatory communication, information transparency, and innovation in public affairs practices to improve the effectiveness of public policy implementation.